Design of wideband phase shifter with edge-coupled semi-elliptical lines. (August 2021) - Lo, Y.C.; Chung, B.K.; Lim, E.H.
Abstract: The analysis and design of a wideband phase shifter using semi-elliptical edge-coupled structure is presented. An elliptical defected ground plane at the bottom layer is also incorporated to increase the coupling coefficient and operating bandwidth. Even and odd mode analysis has been performed and sets of design graphs are formulated to facilitate the design of the phase shifter on substrate with dielectric constant of 2.2 and 3.38. The differential phase shift is controlled by the coupling factor while the operating frequency is determined by the physical dimensions. Both simulation and measurement results show that the proposed design exhibits wideband characteristic with a phase deviation within ±4°, an insertion loss less than 1 ​dB and a return loss better than 10 ​dB. The achievable bandwidth is more than 2.4 : 1 for coupling factor of 5 ​dB which gives a differential phase shift of 80°.